“Eu não vejo muitos negros aqui” uma etnografia sobre a política nacional de saúde integral da população negra em Maceió - Santos, Roberta Dayanne de Oliveira (2017)
The dissertation discusses the National Policy of Integral Health of the Black Population as a biopolitics, whose objective is to "make live" the group of people for whom it is intended. On the occasion of the ethnographic investigation that occurred in several places of the city of Maceió, it was possible to assimilate from which place the interlocutors emit their opinions and the varied interpretations made of the document. This interpretive diversity is strongly linked to the multiple meanings found in the research about what it is to be black in Brazil. Racism emerges as a central element of debate, strongly linked to the triple invisibility that surrounds the argument, namely: the invisibility of a poster, the black and the national health policy of the black population. While a document that legitimates health rights and recognizes the social fragility in which Brazilian blacks are inserted, this public policy is an instrument that starts from the Ministry of Health in line with the demands of social movements, through which it is intended to change the behavior of health professionals at the time of care. The State is also analyzed as having the power to legitimize rights over the health needs of the black population and how biopolitics serve as a key element for such interventions.